Search for the Higgs boson in H -> WW(*) decays in p(p)over-bar collisions at root(s)=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Soc, 2006)
We present a search for the standard model Higgs boson in H -> WW(*) decays with e(+)e(-), e(+/-)mu(-/+), and mu(+)mu(-) final states in p (p) over bar collisions at a center-of-mass-energy of root s = 1.96 TeV. The data, collected from April 2002 to june 2004 with the D0 detector, correspond to an integrated luminosity of 300-325 pb(-1), depending on the final state. The number of events observed is consistent with the expectation from backgrounds. Limits from the combination of all three channels on the Higgs boson production cross section times branching ratio sigma x BR(H -> WW(*)) are presented.